2017
DOI: 10.3389/fpls.2017.00385
|View full text |Cite
|
Sign up to set email alerts
|

Translation and Co-translational Membrane Engagement of Plastid-encoded Chlorophyll-binding Proteins Are Not Influenced by Chlorophyll Availability in Maize

Abstract: Chlorophyll is an indispensable constituent of the photosynthetic machinery in green organisms. Bound by apoproteins of photosystems I and II, chlorophyll performs light-harvesting and charge separation. Due to the phototoxic nature of free chlorophyll and its precursors, chlorophyll synthesis is regulated to comply with the availability of nascent chlorophyll-binding apoproteins. Conversely, the synthesis and co-translational insertion of such proteins into the thylakoid membrane have been suggested to be inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 51 publications
(83 reference statements)
2
19
0
Order By: Relevance
“…Although pulse labeling can reveal protein synthesis rates, it cannot unambiguously distinguish between the absence of synthesis and rapid degradation of newly synthesized proteins (especially not for proteins with high turnover rates, such as PsbA). A recent ribosome profiling analysis of plastid translation in a maize mutant with knocked-out chlorophyll synthesis showed that the synthesis of plastid-encoded chlorophyll binding apoproteins is virtually unaltered in the absence of chlorophyll (Zoschke et al, 2017). Even the cotranslational thylakoid membrane engagement of nascent apoproteins was shown to be independent of chlorophyll synthesis (Zoschke et al, 2017).…”
Section: Developmental Regulation Of Translationmentioning
confidence: 99%
“…Although pulse labeling can reveal protein synthesis rates, it cannot unambiguously distinguish between the absence of synthesis and rapid degradation of newly synthesized proteins (especially not for proteins with high turnover rates, such as PsbA). A recent ribosome profiling analysis of plastid translation in a maize mutant with knocked-out chlorophyll synthesis showed that the synthesis of plastid-encoded chlorophyll binding apoproteins is virtually unaltered in the absence of chlorophyll (Zoschke et al, 2017). Even the cotranslational thylakoid membrane engagement of nascent apoproteins was shown to be independent of chlorophyll synthesis (Zoschke et al, 2017).…”
Section: Developmental Regulation Of Translationmentioning
confidence: 99%
“…To elucidate the role of ribosome-bound cpSRP54 in translation or cotranslational targeting of plastid-encoded thylakoid membrane proteins, a previously described ribosomal profiling approach was used that distinguishes between membrane-associated and soluble footprints and identifies the regions of cotranslational membrane engagement in nascent peptides (Zoschke and Barkan, 2015;Zoschke et al, 2017). To this end, ribosome footprints from separated (thylakoid) membrane and soluble (stroma) fractions of the wild-type Arabidopsis plants and a mutant lacking cpSRP54 (ffc; Amin et al, 1999) were isolated and analyzed by hybridization to microarrays with highly tiled probes covering all chloroplast reading frames.…”
Section: The Cpsrp54-deficient Arabidopsis Ffc Mutant Exhibits An Altmentioning
confidence: 99%
“…We cannot distinguish whether this is caused by features of the mRNA and/or nascent chain 322 or is itself dependent on the incorporation of cofactors. A recent analysis found no changes in translation 323 elongation in mutants of chlorophyll synthesis, indicating that at least chlorophyll supply does not influence 324 ribosome pausing (Zoschke et al, 2017). It is known that Mn 4 CaO 5 cluster binds to D1 and CP43.…”
mentioning
confidence: 96%